Growing Motivation Entrepreneurship: Implementation of Entrepreneurship Education for Vocational School Students - Hanis Bachrodin; Dika Ayu Adininggar (International Journal of Economics and Management Research, 2024)
This research aims to explore the effectiveness of implementing entrepreneurship education at Gudo Vocational School, Jombang in fostering entrepreneurial motivation in students. Through a qualitative approach, data was collected through in-depth interviews and observations of student participation in entrepreneurial activities. The research results show that entrepreneurship education at Gudo Vocational School has an impact on students' motivation to become entrepreneurs. Factors such as practical learning, coaching by experienced teachers, and stimulation to innovate encourage students to consider an entrepreneurial career. The implications of these findings emphasize the importance of strengthening entrepreneurship education in secondary education institutions, which can provide a strong foundation for students to develop entrepreneurial skills and prepare them to become key drivers in an economy based on creativity and innovation.